Foundational African writers : Peter Abrahams, Noni Jabavu, Sibusiso Nyembezi and Es'kia Mphahlele - Peterson, Bhekizizwe; Mkhize, Khwezi; Xaba, Makhosazana (Wits University Press, 2022)
A collection of essays celebrating the centenaries of Peter Abrahams, Noni Jabavu, Sibusiso Nyembezi and Es'kia Mphahlele, all born in South Africa in 1919. These foundational writers produced fiction, criticism, journalism and life writing, and their oeuvres are crucial to the genealogies of modern African and diasporic black literature.